Study on Optimization of Blast Design for Improving Fragmentation in Jeju Basalt Rock Area - Jang, Hyong Doo; Yang, H.; Kim, N.; Kim, W.; Ko, Y.; Kim, S.; Kim, J.; Mon, H. (Korean Society of Explosives & Blasting Engineering, 2011)
Recently on Jeju island there has been a lot of development and construction. However random distribution of porous basalt and clinker seam generated from volcanic activities often interrupt and greatly reduce efficiency of blasting necessary for construction. Three test blasts were operated to solve the inefficiency problem and results indicated that a powder factor of 0.40~0.45 kg/cm3 is necessary to increase the efficiency of blasting. Also the blasting scheme should be concerned whether clinker seams exists in excavation levels or not.